2016
DOI: 10.5194/bg-13-3793-2016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of transparent exopolymer particles (TEP) during the VAHINE mesocosm experiment in the New Caledonian lagoon

Abstract: In the marine environment, transparent exopolymeric particles (TEP) produced from abiotic and biotic sources link the particulate and dissolved carbon pools and are essential vectors enhancing vertical carbon flux. We characterized spatial and temporal dynamics of TEP during the VAHINE experiment that investigated the fate of diazotroph-derived nitrogen and carbon in three replicate dissolved inorganic phosphorus (DIP)-fertilized 50 m 3 enclosures in the oligotrophic New Caledonian lagoon. During the 23 days o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 69 publications
(122 reference statements)
4
28
0
Order By: Relevance
“…4c, p<0.05 (Fig. 4c) (Spungin et al, 2016). 493 TEP concentrations at LDB were positively correlated to TOC, POC, and DOC ( Fig.…”
Section: Diazotrophic Bloom Demise In the Ld Stations 348mentioning
confidence: 83%
“…4c, p<0.05 (Fig. 4c) (Spungin et al, 2016). 493 TEP concentrations at LDB were positively correlated to TOC, POC, and DOC ( Fig.…”
Section: Diazotrophic Bloom Demise In the Ld Stations 348mentioning
confidence: 83%
“…This indicates that UCYN-C cannot only contribute to direct export but promote indirect export. The high content of TEP measured in traps by Berman-Frank et al (2016) on days 15 and 16 in correlation with the increase in UCYN-C abundances observed by led to the assumption that the presence of TEP in the field would facilitate export flux and especially the sinking of UCYN-C during P2. This phenomenon was taken into account in the model by allowing, each day from day 10, the settling of 10 % of all the model compartments (living and non-living, particulate and dissolved) in addition to the detrital particulate matter.…”
Section: An Expected Enhancement Of Biogeochemical Fluxes After the Dmentioning
confidence: 86%
“…Finally, the overestimation of UCYN-C abundance by the model also supports the idea that UCYN-C sinking is underestimated by the model. The aggregation process induced by TEP (Berman-Frank et al, 2016) or by specific molecules such as extracellular polysaccharides (EPSs; Sohm et al, 2011), which is not explicitly represented in the model, might explain the preferential export of UCYN-C in the mesocosms. Hence, though aggregation was probably overestimated in the mesocosms as compared to natural situations, the contribution of this process seems to be significant in C export.…”
Section: Discussion On the Time Duration Of Enrichment Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bottom panel: simplified evolution of the major standing stocks, rates and plankton abundances measured during P1 (days 5 to 14) and P2 (days 15 to 23). Protocols for each parameter measurements are described in Berthelot et al (2015b), Bonnet et al (2016a, b), Van Wambeke et al (2016), Berman-Frank et al (2016), Leblanc et al (2016), Turk-Kubo et al (2015) and Hunt et al (2016). Squares are represented in green when a significant (p < 0.05) increase was observed between each period (i.e.…”
Section: Sampling Strategy and Logisticsmentioning
confidence: 99%